Electro-oxidation to convert dissolved organic nitrogen and soluble non-reactive phosphorus to more readily removable and recoverable forms. (September 2021) - Mallick, Synthia P.; Ryan, Donald R.; Venkiteshwaran, Kaushik; McNamara, Patrick J.; Mayer, Brooke K.
Abstract: Conventional wastewater treatment processes cannot effectively remove dissolved organic nitrogen (DON) and soluble non-reactive phosphorus (sNRP), which can pose regulatory compliance challenges for total nitrogen and total phosphorus discharges. Moreover, DON and sNRP are not easily recoverable for beneficial reuse as part of the waste to resource paradigm. Conversion of DON and sNRP to more readily removable dissolved inorganic nitrogen (DIN) and soluble reactive phosphorus (sRP), respectively, will help meet stringent nutrient limits and facilitate nutrient recovery. In this study, electro-oxidation (EO) was evaluated for conversion of four DON compounds to DIN and five sNRP compounds to sRP. EO was more efficient and provided higher extents of conversion of the recalcitrant nutrient fractions compared to a more traditional advanced oxidation process, UV/H2 O2 . Direct electron transfer was likely the dominant oxidation mechanism for EO-based DON and sNRP conversion, with DON being more recalcitrant. Among the DON compounds tested, greater availability of primary amine (C–N bonds) yielded greater conversion compared to compounds with fewer primary amine or those with secondary amine (C–N–C bond). Among the sNRP compounds tested, those with P–O–C bonds (organic sNRP) converted more readily than those with P–O–P bonds (inorganic sNRP), presumably because cleavage of the latter bond requires greater energy. Using 30 min of EO treatment, the highest DON and sNRP compound conversion was 11.7 ± 0.09% for urea and 31.1 ± 0.75% for beta-glycerol phosphate. A similar extent of EO-based conversion of DON (6.41 ± 1.5%) and sNRP (32.7 ± 3.3%) was observed in real wastewater. Highlights: Electro-oxidation (EO) converts DON and sNRP more efficiently than UV/H2 O2 . sNRP conversion to removable/recoverable P was more efficient than DON conversion. Organic sNRP was more susceptible to EO-based conversion compared to inorganic sNRP. Direct electron transfer was likely the dominant mechanism for EO-based conversion. The wastewater matrix did not significantly inhibit sNRP conversion.